Improvement of depressive symptoms, after a suicide attempt, with dextromethorphan/bupropion combination treatment in a patient with treatment‐resistant depression and psychiatric comorbidities. Issue 3 (7th March 2023) - Pedraz‐Petrozzi, Bruno; Deuschle, Michael; Gilles, Maria
Abstract: We admitted a 42‐year‐old patient with severe treatment‐resistant depression and with psychiatric comorbidities. The patient attempted suicide 5 weeks after admission. Subsequently, we initiated dextromethorphan/bupropion based on prior evidence. As a result, the patient demonstrated an improvement in mood symptoms and a reduction in suicide risk, leading to her discharge.